2010
DOI: 10.1123/ijsnem.20.3.236
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Supplementation Before Squat Exercise and Delayed-Onset Muscle Soreness

Abstract: The authors examined the effect of branched-chain amino acid (BCAA) supplementation on squat-exercise-induced delayed-onset muscle soreness (DOMS) using 12 young, healthy, untrained female participants. The experiment was conducted with a crossover double-blind design. In the morning on the exercise-session day, the participants ingested either BCAA (isoleucine:leucine:valine = 1:2.3:1.2) or dextrin at 100 mg/kg body weight before the squat exercise, which consisted of 7 sets of 20 squats/set with 3-min interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
3
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 42 publications
(56 reference statements)
12
106
3
11
Order By: Relevance
“…These effects were in accordance with the experimental hypotheses. The findings support previous literature suggesting BCAA can be supplemented to relieve the negative effects of muscle damaging exercise [13,23] and more specifically damaging resistance exercise [24][25][26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These effects were in accordance with the experimental hypotheses. The findings support previous literature suggesting BCAA can be supplemented to relieve the negative effects of muscle damaging exercise [13,23] and more specifically damaging resistance exercise [24][25][26].…”
Section: Discussionsupporting
confidence: 80%
“…The ST was designed to replicate the demands of traditionally practiced athletic strength sessions, rather than predominantly focus on inducing extreme levels of EIMD and subsequent decrements in functional performance and elevations in markers of muscle damage [16,27]. Repetitive high force, eccentric muscle actions, as used by Howatson et al, [2], result in amplified EIMD, as witnessed by the vast decrements in maximal voluntary contraction (~20-27%) [5,26] and increments in RMS across groups [2,29]. This is relevant, as contemporary research has shown that perceptible effects on muscle function, created through prophylactic interventions such as BCAA ingestion, are likely to be more noticeable under conditions of greater muscle damage [30].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in flexed muscle soreness was observed in supplemented compared with placebo group at 48 h and 72 h post exercise whereas the degree of force loss and the fluctuation of blood markers of muscle damage appeared unchanged between groups [186]. Similar results were obtained in female untrained young subjects by Shimomura et al [187] examining the effects of BCAA supplementation on squat-exercise-induced DOMS. In this report the participants ingested either BCAA (isoleucine:leucine:valine = 1:2.3:1.2) or dextrin at 100 mg/kg body weight just before the squat exercise consisting of 7 sets of 20 squats/set with 3-min intervals between sets.…”
Section: Essential Amino Acidssupporting
confidence: 75%
“…Interestingly three day post exercise the force decrease observed in the placebo appeared to be prevented by BCAA supplementation. Accordingly plasma myoglobin and elastase (index of neutrophil activation) appeared to be increased by exercise in the placebo but not in the BCAA group [187].…”
Section: Essential Amino Acidsmentioning
confidence: 99%
“…Delayed-onset muscle soreness (DOMS), which is most strongly felt at 24 to 72 h after exercise, is caused by non-routine or strenuous exercise. The effects of BCAA supplementation on squat exercise-induced DOMS has been examined using untrained young women [29][30][31] ; and these studies demonstrated that BCAA supplementation before exercise significantly reduces the level of DOMS. This effect has also been demonstrated in male subjects 32) .…”
Section: Increased Amino Acid Breakdown By Exercisementioning
confidence: 99%